2016
DOI: 10.4103/2347-5625.177390
|View full text |Cite
|
Sign up to set email alerts
|

Emotional aspects and pranayama in breast cancer patients undergoing radiation therapy: A randomized controlled trial

Abstract: Objective:Emotional disturbances are commonly experienced by cancer patients. The aim of this study was to determine the effectiveness of certain Pranayama techniques on the emotional aspects such as impatience, worry, anxiety, and frustration among breast cancer patients undergoing radiation therapy in India.Methods:The study was conducted as a randomized controlled trial. Patients were recruited when they were seeking radiation therapy for breast cancer. They were allocated into two groups using block random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Three studies were reported in patients with breast carcinoma, whereas the other studies involved patients with different types of malignant diseases undergoing chemoradiotherapy. [ 21 23 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies were reported in patients with breast carcinoma, whereas the other studies involved patients with different types of malignant diseases undergoing chemoradiotherapy. [ 21 23 ]…”
Section: Resultsmentioning
confidence: 99%
“…assessed the effect of pranayama on cancer-related fatigue and emotional aspects of breast cancer patients ( n = 160) undergoing radiation therapy. [ 21 23 ] Fatigue level was assessed using the cancer fatigue scale, and emotional aspects were assessed using five items as part of the assessment of cancer-related fatigue. The study results indicated a significant difference ( P < 0.001) in the pre- and post-test scores of cancer-related fatigue in the interventional group compared to the control group ( P < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…Patients are also recommended various forms of psychotherapy [ 10 , 11 , 12 ], such as relaxation and guided imagery [ 13 , 14 ], mindfulness meditation (mindfulness-based stress reduction) [ 14 ], music therapy [ 15 , 16 ], occupational therapy [ 17 , 18 , 19 ], and breathing exercises [ 20 , 21 , 22 ]. Most of the mentioned therapies are a part of vinyasa yoga training, which always includes breath work ( Pranayama ) and relaxation ( Shavasana ), enhanced by aromatherapy, music therapy, or/and visualization techniques or Nidra yoga.…”
Section: Introductionmentioning
confidence: 99%